The relationship between striatal dopamine and anterior cingulate glutamate in first episode psychosis changes with antipsychotic treatment - Jauhar, S; McCutcheon, RA; Veronese, M; Borgan, F; Nour, M; Rogdaki, M; Pepper, F; Stone, JM; Egerton, A; Vamvakas, G; Turkheimer, F; McGuire, PK; et al. (Springer Nature, 2023)
The neuromodulator dopamine and excitatory neurotransmitter glutamate have both been implicated in the pathogenesis of psychosis, and dopamine antagonists remain the predominant treatment for psychotic disorders. To date no study has measured the effect of antipsychotics on both of these indices together, in the same population of people with psychosis. Striatal dopamine synthesis capacity (Kicer) and anterior cingulate glutamate were measured using 18F-DOPA positron emission tomography and proton magnetic resonance spectroscopy respectively, before and after at least 5 weeks’ naturalistic antipsychotic treatment in people with first episode psychosis (n = 18) and matched healthy controls (n = 20). The relationship between both measures at baseline and follow-up, and the change in this relationship was analyzed using a mixed linear model. Neither anterior cingulate glutamate concentrations (p = 0.75) nor striatal Kicer (p = 0.79) showed significant change following antipsychotic treatment. The change in relationship between whole striatal Kicer and anterior cingulate glutamate, however, was statistically significant (p = 0.017). This was reflected in a significant difference in relationship between both measures for patients and controls at baseline (t = 2.1, p = 0.04), that was not present at follow-up (t = 0.06, p = 0.96). Although we did not find any effect of antipsychotic treatment on absolute measures of dopamine synthesis capacity and anterior cingulate glutamate, the relationship between anterior cingluate glutamate and striatal dopamine synthesis capacity did change, suggesting that antipsychotic treatment affects the relationship between glutamate and dopamine.